Peran Profitabilitas Dalam Memoderasi Pengaruh Struktur Modal Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019 - Ia Siti Bahriah; Nor Norisanti; R Deni Muhammad Danial (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to determine the effect of capital structure and firm size on firm value by moderating profitability in food & beverages companies. Samples are Food & Beverages Sub Sector manufacturing companies listed on the Indonesia Stock Exchange in the 2017-2019 period, which were taken using purposive sampling technique. The analysis technique used is a moderation regression analysis (MRA) using SPSS 26. The results of hypothesis testing show that the capital structure variable (DER) has a positive and significant effect on firm value (PBV), firm size (SIZE) has a negative and does not significant effect on firm value ( PBV), profitability (ROE) strengthens the effect of capital structure (DER) on firm value (PBV), profitability (ROE) strengthen the effect of firm size (SIZE) on firm value (PBV). Keywords: Capital Structure, Firm Size, Profitability, Firm Value